A qualitative evaluation of pharmacy technician opinions about administering immunizations - Kimberly C. McKeirnan; Elyssa Hanson (Elsevier, 2023)
Introduction: Pharmacy technicians began administering immunizations in Idaho State as part of a new administrative rule in 2017. Rapid expansion of pharmacy technicians as immunizers occurred during the COVID-19 pandemic. Previous studies demonstrate the success of having technicians as immunizers but, the opinions of technicians themselves about immunizing have not been explored. Methods: Key informant interviews were conducted to evaluate the opinions of certified and immunization-trained pharmacy technicians in the State of Idaho. A key informant interview script was utilized and included questions regarding satisfaction with current position, feelings about responsibility in the pharmacy, confidence administering immunizations to patients, changes patient interactions after becoming immunization-trained, support in the pharmacy, and opinion about expansion of immunization training for technicians to other states. The aim of this research was to gather the opinions of pharmacy technicians regarding the impact of administering immunizations on job satisfaction and career outlook. Results: Fifteen pharmacy technicians were interviewed. All participants believed their role as immunizers improved job satisfaction and feelings of being a valuable part of the pharmacy team. Technicians also believed being able to immunize aided in pharmacy workflow, decreased wait time for immunizations at their respective pharmacies, and increased the number of immunizations being administered. Respondents also believed technicians should be allowed to administer immunizations nation-wide but also felt strongly that the decision to immunize should be up to each individual pharmacy technician. Conclusion: Immunizing technicians in this study believe that this advanced role has had a positive impact on their job satisfaction, feeling valued in the workplace, and likelihood of staying in their current position. Immunizing has also led to positive engagement with patients and beliefs that they are providing an impactful service to their communities.